Unusual Events Detection via Global Optical Flow and SVM - Sujatha, S; Mendonca, Alwyn Edison (International Journal of Computer Sciences and Engineering, 2025)
Detection of unusual events in video streams, for the purpose of investigation and security is a challenging technology in crowded scenes. To address this issues, an algorithm is proposed, which is based on Histogram of Optical Flow Orientation image descriptor and nonlinear one-class SVM classification method. The optical flow method is computed at each pixel to extract the low-level features. Histogram of Optical Flow Orientation descriptor encoding the global moving information of each frame and one-class support vector machine classifier detects the unusual events in the current frame, after learning period distinguishing the common behaviors of the training frame. k nearest neighbor classifier is used to classify the abnormal frames in video streams. Further, by combining the background subtraction step and optical flow computation, a improved version of the detection algorithm is designed. This proposed method works on several benchmark datasets to detect unusual events. Histogram of optical flow orientation with nonlinear one-class SVM classifier shows the high performance result than, k nearest neighbor classifier with histogram of optical flow orientation.